Successful treatment with allogeneic stem cell transplantation followed by DLI and TKIs for e6a2 BCR-ABL-positive acute myeloid leukaemia: A case report and literature review. Issue 50 (December 2017) - Harada, Yasuhiko; Nishiwaki, Satoshi; Sugimoto, Takumi; Onodera, Koichi; Goto, Tatsunori; Sato, Takahiko; Kamoshita, Sonoko; Kawashima, Naomi; Seto, Aika; Okuno, Shingo; Yamamoto, Satomi; Iwasaki, Toshihiro; et al.
Abstract: Rationale: Patients with the e6a2 BCR-ABL transcript, 1 of the atypical transcripts, have been reported to have a poor prognosis, and allogeneic stem cell transplantation (ASCT) can be considered as additional therapy. However, long-term survival after ASCT for this disease is rare. Patient concerns: This report concerns a 55-year-old female patient with e6a2 BCR-ABL -positive acute myeloid leukemia including the outcome of ASCT followed by donor lymphocyte infusion (DLI). Diagnoses: The breakpoint was confirmed by direct sequencing. Her minimal residual disease could be detected by nested reverse-transcription polymerase chain reaction using primers for the minor BCR-ABL (e1a2) transcript. Interventions: Treatment with tyrosine kinase inhibitors (TKIs) and ASCT followed by DLI. Outcomes: Despite multiple cytogenetic and molecular relapses after ASCT, she remains in molecular remission at 46 months after ASCT. Lessons: This case indicates the efficacy of the combination of the graft-versus-leukemia effect and TKIs for e6a2 BCR-ABL -positive acute leukemia. When the Philadelphia chromosome with an unusual chromosomal breakpoint is suggested, we should clarify the breakpoint because that information can aid molecular assessments and decisions to provide an additional or alternative therapy.